The Preparation and Reactivity of 2-Bromo-3-(tri-n-butylstannyl)-1-propene - Williams, David R.; Shah, Akshay A.; Brooks, Dawn A.; Zorn, Nicolas (Synlett, 2016)
The preparation of 2-bromo-3-(tri-n-butylstannyl)-1-propene is described. This study characterizes the reactivity of 2-bromo-3-(tri-n-butylstannyl)-1-propene in SE′ reactions with aldehydes and includes a survey of radical reactions of 2-bromo-3-(tri-n-butylstannyl)-1-propene with α-bromocarbonyl compounds for C-alkylation.
Keywords: organostannane preparation; bifunctional reagent; SE′ reactions; radical reaction; alkenyl bromides